Utilization of Moringa Leaves as a Mathematics Learning Media at Elementary/Islamic Elementary School - Nursupiamin Nursupiamin (Institut Agama Islam Negeri Palopo, 2020)
The study of the use of Moringa a leaf in mathematics learning at elementary / Islamic elementary level as an alternative media for learning mathematics based on local wisdom aims to introduce the use of Moringa leaves in mathematics learning, especially in the concept of counting and connections in making patterns. The method applied is a literature review obtained through the Research Gate and Google Scholar databases and other relevant sources. Data were analyzed using descriptive analysis method. Based on this study, it is known that in addition to its role in culinary and treatment, Moringa leaves can also be used as a medium for learning mathematics, especially in applying the concept of arithmetic at the elementary / Islamic elementary level and in making connections. So according to this, it is expected that the study can be used as a reference in developing the creative potential of teachers and students in order to create the characteristics of effective and efficient mathematics learning.